Legal Aid in Indonesia: Problems and Challenges - Gustaf, Muhammad Akbar Maulana (The Indonesian Journal of International Clinical Legal Education, 2021)
In the 1945 Constitution of the Republic of Indonesia Article 28D Paragraph (1), it is stated that "Everyone has the right to recognition, guarantee, protection and legal certainty that is just and equal treatment before the law." Legal aid is legal services provided by legal aid providers free of charge to legal aid recipients, namely people or groups of poor people to obtain justice. Legal Aid Providers are legal aid organizations or social organizations that provide Legal Aid services based on Law no. 16 of 2011 concerning Legal Aid. With free legal assistance, people who are unable, in this case at the economic level, who are involved in the judicial process will receive relief from obtaining legal advisors so that their rights can be protected and the judicial process can proceed properly.